P1-S1.52 Incidence of Anal HPV and HPV-related sequelae in HIV-infected and uninfected US adolescents. (10th July 2011) - Mullins, T; Wilson, C; Rudy, B; Sucharew, H; Kahn, J
Abstract : Background: Immunodeficiency related to HIV infection may place HIV-infected youth at increased risk of human papillomavirus (HPV) infection and anal dysplasia. Our objective was to determine incidence of anal HPV infection and related sequelae, and factors associated with these outcomes, among adolescents who are HIV-infected or -uninfected but at-risk. Methods: We analysed data from the Reaching for Excellence in Adolescent Care and Health Project. Adolescents age 12–18 years who were behaviourally HIV-infected (n=319) or -uninfected but at risk (n=177) were recruited at 15 US sites from 1996 to 1999. Incidence rates for anal HPV, high risk anal HPV, anogenital warts, and anal dysplasia were calculated using Poisson modelling. Factors associated with these outcomes were explored using Cox proportional hazards modelling. Results: Mean age at entry was 16.8 years, and mean follow-up time for detection of anal HPV infection was 22.4 months (SD 10.8). Most participants (76%) were female, and 70% were black non-Hispanic. HIV-infected women (vs -uninfected women) had higher incidence of anal HPV (30 vs 14 per 100 person-years; p=0.002), high risk anal HPV (12 vs 5.3 per 100 person-years; p=0.04), and anogenital warts (6.7 vs 1.6 per 100 person-years; p=0.002) but not anal dysplasia. Although incidence rates of these outcomes were consistently higher among HIV-infected vs -uninfected men, they did not achieve statistical significance. Factors associated with incident anal HPV, high risk anal HPV, anogenital warts, and anal dysplasia in women are shown in the Abstract P1-S1.52 table 1 below. No factors were associated with any outcome in men. Conclusions: HIV-infected women, when compared to HIV-uninfected women, had higher rates of HPV and related sequelae. Because HIV-infected youth are at increased risk of HPV and related disease, enhanced HPV prevention efforts, such as vaccination, are warranted for this group.